SIX1 Downregulation Suppresses Self-renewal Capacity and THY1 Expression in Hepatocellular Carcinoma and SIX1 Dominate the Survival in Liver Cancer - Balçık-Erçin, Pelin; Aysan, Arzu; Salık, Nazlı; Erciyas, Esma (Turkish Journal of Gastroenterology, 2023)
Background/Aims: Sine oculis homeoprotein 1 exerts an essential role in embryonic development, and it was also identified to be reactivated in various types of mammalian cancer. The sine oculis homeoprotein 1 transcription factor was demonstrated to induce epithelial–mesenchymal transition, regulate crucial genes associated with cancer progression, and increase the oncogenic potential of cells. Therefore, the present study aimed to identify the role of sine oculis homeoprotein 1 in cancer. Materials and Methods: Sine oculis homeoprotein 1 gene expression was tested with real-time quantitative polymerase chain reaction (PCR) in different cancer types. Sine oculis homeoprotein 1 expression was suppressed by short hairpin RNA transduction in the SNU398 hepatocellular carcinoma cell line. The effects of sine oculis homeoprotein 1 on cell proliferation, drug resistance, and sphere formation were assessed in shSIX1 cells. Immunohistochemical and in silico analyses were performed to determine the prognostic role of sine oculis homeoprotein 1 expression. Results: The upregulated expression levels of sine oculis homeoprotein 1 were revealed to be correlated with the stage of the disease in breast, colon, and liver cancer, with liver cancer exhibiting the highest expression profile. Sine oculis homeoprotein 1 downregulation significantly affected cell proliferation and suppressed sorafenib resistance and sphere-forming ability. Furthermore, sine oculis homeoprotein 1 knockdown cells were identified to have decreased CD90 levels, essential for cancer stem cell properties. Finally, sine oculis homeoprotein 1 expression was a CD90-independent biomarker for the clinical prognosis of liver cancer. Conclusion: The results of this study showed that the knockdown of sine oculis homeoprotein 1 expression might help to prevent hepatocarcinogenesis by increasing drug sensitivity and controlling tumor sphere formation. Overall, these results indicated that sine oculis homeoprotein 1 expression might be useful as a diagnostic marker for patients with hepatocellular carcinoma. Cite this article as: Balçık-Erçin P, Aysan A, Salık N, Erciyas E. SIX1 downregulation suppresses self-renewal capacity and THY1 expression in hepatocellular carcinoma and SIX1 dominate the survival in liver cancer. Turk J Gastroenterol. 2023;34(8):881-889.